2020
DOI: 10.1061/(asce)hy.1943-7900.0001817
|View full text |Cite
|
Sign up to set email alerts
|

Shock-Fitting Approach for Calculating Air Pocket Entrapment Caused by Full Obstruction in Closed Conduit Transient Flow

Abstract: This paper studies the ability of a Shock-Fitting approach in computing air pocket entrapments in a closed conduit transient flow, caused by suddenly blocking the downstream end. The flow is pressurized at the upstream, which detaches from the wall somewhere at the downstream after which a free surface flow develops. In this Shock-Fitting approach a pressurized flow is simulated by the rigid column model and the free surface flow is simulated by the Saint-Venant equations set. A transient region, which is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, the backward Euler implicit scheme has been used in [13] to simulate the dynamics of the entrapped air pocket using the 3D Navier-Stokes equation and the volume of fluid (VOF) method. In addition, Rokhzadi and Fuamba [14] proposed using the backward Euler implicit scheme to solve a similar problem by a shock-fitting approach.…”
Section: Liou and Huntmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the backward Euler implicit scheme has been used in [13] to simulate the dynamics of the entrapped air pocket using the 3D Navier-Stokes equation and the volume of fluid (VOF) method. In addition, Rokhzadi and Fuamba [14] proposed using the backward Euler implicit scheme to solve a similar problem by a shock-fitting approach.…”
Section: Liou and Huntmentioning
confidence: 99%
“…Rokhzadi and Fuamba [14], for problems with small ratios of the reservoir pressure to the atmospheric pressure, used a shock-fitting approach, which is a combination of the RC model and the Saint-Venant equations. Rokhzadi and Fuamba proposed using the BE scheme instead of the 4th-RK scheme.…”
Section: Effective Time Step Sizementioning
confidence: 99%
“…In addition, this method is able to automatically handle the supercritical conditions that may occur in the free-surface flow zone because interface fluxes are calculated by solving a Reimann problem (León et al 2010). Rokhzadi and Fuamba (2020), using the shock-fitting approach, which is a combination of the RC model and the Saint-Venant equations, calculated an air pocket entrapment problem in a partially pressurized transient flow. They showed that, compared to the fourth-order Runge-Kutta explicit time integration scheme, the dissipation property of the backward Euler implicit scheme can take the extra energy, which is left due to the RC model assumptions (Malekpour and Karney 2014) as well as due to neglecting the heat transfer process between the air and pipe wall (Lee 2005).…”
Section: Introductionmentioning
confidence: 99%